THE COHESION AND COHERENCE IN BARACK OBAMA’S SPEECH TEXT “FINAL PRESIDENTIAL PRESS CONFERENCE OF YEAR” - Deta Hardiyanto Harefa (Universitas Nias Raya, 2023)
This research aimed at analyzing the cohesion and coherence in Barack Obama’s speech text “Final presidential press conference of year”. This research designed by the qualitative method with descriptive approach. Then, researcher used the Miles, Huberman, & Saldana theory to analyze the cohesion and coherence in the speech text. The result of this research showed all of cohesion and coherence devices were found. The data of this research were words and phrases. Based on summary of the result, that Barack Obama’s speech text “Final Presidential Press Conference of Year” contained grammatical cohesion devices, they are reference (34), subtitution (1), ellipsis (12), and conjuntion (60). And then, it contained the lexical cohesion devices. They are; reiteration (47) and collocation (11). Moreover, it contained the coherence devices. They are; repeat key nouns (9), consistent pronoun (5), transition signals (53), and the ideas in the speech text are arranged structurally. Based on the research finding, in the spech text, the cohesion devices dominanted in grammatical cohesion, especially in using conjuction. And the coherence devices dominanted in using transition signals. It is suggested that English learners’ should pay attention about the usage of cohesion and coherence in order to create a good text as well as a speech. For the teachers, hopefully this research could be used to enrich their teaching material. And for the next researcher, can get information and knowledge to create a text grammatically and semantically.